A Single-Stage Regulating Voltage-Doubling Rectifier for Wireless Power Transfer - Lu, Tianqi; Du, Sijun (IEEE solid-state circuits letters, 2023)
In this letter, a 6.78-MHz single-stage regulating voltage-doubling rectifier is presented for biomedical wireless power transfer (WPT) applications. Derived from a full-wave voltage doubler, a theoretical voltage conversion ratio (VCR) of 2 can be achieved, which benefits the end-to-end voltage gain of a biomedical WPT system with varying link conditions. As a result, a wider WPT operational range and less coil-link loss can be achieved. To avoid efficiency loss due to cascading, the rectifier output is in-situ regulated in a sub-50-mV hysteresis window by pulse-skipping control. To ensure a high power conversion efficiency (PCE), adaptive delay-compensated active diodes are adopted with an offset locking technique. The input/output capacitors of the rectifier are fabricated on-chip, achieving a fully integrated design. The rectifier was fabricated in a 180-nm BCD process, occupying a silicon area of 0.3/2.7 mm2 without/with on-chip capacitors. The measurements show that the rectifier can realize a peak PCE at 90.6% when the output power is 79.8 mW. The PCE and VCR are achieved higher than 86.4% and 1.6, respectively, over a large loading range (from 1 to 40 mA). The rectifier can output a maximum power of 159.2 mW, satisfying most biomedical implants.